A Comparative Analysis of the Financial Performance Based on Financial Ratios - Niken Dania Purwati; Ruly Wiliandri (Institut Teknologi dan Bisnis Asia Malang, 2026)
This study compares the financial performance of the governments of Malang Regency, Malang City, and Batu City during 2020–2024 using seven indicators: PAD effectiveness, expenditure-to-PAD efficiency, dependence on central government transfers, capital expenditure ratio, operational expenditure ratio, and revenue and expenditure growth. Employing a quantitative descriptive-comparative approach, the study analyzes budget realization reports using descriptive statistics, normality tests, and one-way ANOVA. The findings show that all three local governments achieved relatively similar and effective PAD performance, with realization rates ranging from 91% to 101%. However, expenditure-to-PAD ratios remained high (341%–545%), indicating limited fiscal capacity. Dependence on transfer funds was also substantial, reaching 1.78–3.67 times PAD, although Malang City demonstrated comparatively greater fiscal independence. Regional budgets were dominated by operational expenditure (80%–96%), while capital expenditure remained low (11%–14%). Revenue and expenditure growth were unstable across regions. These findings highlight the need to strengthen fiscal autonomy through PAD optimization and budget restructuring toward more productive capital expenditure.